Deciphering the Roles of PPARγ in Adipocytes via Dynamic Change of Transcription Complex - Ma, Xinran; Wang, Dongmei; Zhao, Wenjun; Xu, Lingyan (Frontiers in Endocrinology, 2018)
Peroxisome proliferator-activated receptor γ (PPARγ), a ligand-dependent transcription factor highly expressed in adipocytes, is a master regulator of adipogenesis and lipid storage, a central player in thermogenesis and an active modulator of lipid metabolism and insulin sensitivity. As a nuclear receptor governing numerous target genes, its specific signaling transduction relies on elegant transcriptional and post-translational regulations. Notably, in response to different metabolic stimuli, PPARγ recruits various cofactors and forms distinct transcriptional complexes that change dynamically in components and epigenetic modification to ensure specific signal transduction. Clinically, PPARγ activation via its full agonists, thiazolidinediones, has been shown to improve insulin sensitivity and induce browning of white fat, while undesirably induce weight gain, visceral obesity and other adverse effects. Thus, deciphering the combinatorial interactions between PPARγ and its transcriptional partners and their preferential regulatory network in the processes of development, function and senescence of adipocytes would provide us the molecular basis for developing novel partial agonists that promote benefits of PPARγ signaling without detrimental side effects. In this review, we discuss the dynamic components and precise regulatory mechanisms of the PPARγ-cofactors complexes in adipocytes, as well as perspectives in treating metabolic diseases via specific PPARγ signaling.